tDCS-Induced Memory Reconsolidation Effects: Analysis of Prominent Predicting Factors - Cotelli, Maria; Ferrari, Clarissa; Gobbi, Elena; Binetti, Giuliano; Manenti, Rosa; Sandrini, Marco (Frontiers in Neuroscience, 2022)
Background: Memory impairment is among one of the greatest cognitive complaints in midlife and old age. Considering the importance of good memory functioning in everyday life, it is crucial to study interventions that can reduce the natural decline in this cognitive function. Transcranial Magnetic Stimulation (TMS) studies have demonstrated that the lateral prefrontal cortex (PFC) plays a causal role in enhancing episodic memory recall through reconsolidation. Using a similar paradigm with transcranial direct current stimulation (tDCS) over the left lateral PFC, facilitation effects were observed in delayed memory retrieval in older adults with subjective memory complaints (SMCs) and amnestic Mild Cognitive Impairment (aMCI). However, it remains unclear which potential factors (i.e., tDCS group, cognitive reserve, education level, diagnosis and encoding performance) directly and/or indirectly modulate the tDCS-induced memory reconsolidation effects. Methods: We reanalysed data acquired in our previous tDCS studies with 22 SMC and 18 aMCI participants from the perspective of predicting delayed memory retrieval performance. These studies included a learning session on Day 1, a reactivation by a contextual reminder followed by 15 minutes of tDCS session on Day 2 (24 hours after Day 1), and two retrieval sessions (free recall and recognition) tested on Day 3 and Day 30 (48 hours and 30 Days after Day 1). Results: Univariate models showed that tDCS group (sham vs. active) significantly predicted memory recognition (but not free recall), evidenced by higher scores in the active tDCS group than in sham group, confirming our previous results. Encoding performance and diagnosis (SMC vs. aMCI) significantly predicted memory retrieval, suggesting higher performances in individuals with SMC than in those with aMCI. Regarding cognitive reserve, higher leisure time activity subscores significantly predicted better memory recognition. Finally, multiple models did not show any tDCS group × predictor interaction effects, indicating that the effects of the predictors on retrieval occurred irrespective of tDCS group. Conclusions: Our results shed light on predicting factors of episodic memory retrieval in this reconsolidation paradigm in individuals with SMC and aMCI. The findings suggest that multifactorial interventions program may be most promising to slow cognitive decline and delay the onset of dementia.